2019
DOI: 10.1108/bfj-04-2019-0243
|View full text |Cite
|
Sign up to set email alerts
|

Bringing terroir back to the roots? A methodological proposal for studying local food products

Abstract: Purpose In line with various scientific papers warning against an inconsistent use of this adjective for food qualification, the purpose of this paper is to point out the sweeping assertion that “local” equates to “ecological”. Design/methodology/approach Looking beyond the measurement of carbon emissions to assess impacts on the environment, this paper addresses ecological issues in terms of interactions with the environment. To this end, it enhances an under-the-skin approach that goes through “local” frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Herbón farmers emphasised these localised resources and qualities to justify the distinctiveness of the production and their rights over it. This construction of terroir , given its spatial limitation, served as a discursive framework against the introduction in the GI of other companies (Garçon, 2019). Importantly, some AFN scholars have tended to blame this kind of position as ‘defensive localism’ based on exclusionary practices (DuPuis & Goodman, 2005; May, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbón farmers emphasised these localised resources and qualities to justify the distinctiveness of the production and their rights over it. This construction of terroir , given its spatial limitation, served as a discursive framework against the introduction in the GI of other companies (Garçon, 2019). Importantly, some AFN scholars have tended to blame this kind of position as ‘defensive localism’ based on exclusionary practices (DuPuis & Goodman, 2005; May, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Anglophone‐based relational perspective was also topical for critically studying the construction and validation of terroirs within GI application processes. Demossier (2011), Grasseni (2016) and Garçon (2019) showed that stakeholders can make use of an array of evidence such as historic documents or agronomic measurements to reinforce certain GI territorial bonds and, by doing so, exclude other producers. Meanwhile, other GIs present a weaker product– terroir link with a bias towards tourism development and/or production growth (Alonso & Parga, 2018; Bowen & Zapata, 2009; Brunori & Rossi, 2007).…”
Section: Spatial/territorial Approaches To Food Studies: Two Traditionsmentioning
confidence: 99%
“…Legally recognised terroir also turns into a Protected Designation of Origin (PDO), which can be used as a certification of origin and production processes, such as Brie de Provance (Charters et al, 2017). Currently, terroir branding is applied to a variety of agricultural products and natural resources; however, empirical studies are limited and are often restricted to alcohol (Garçon, 2019; Sjölander‐Lindqvist et al, 2020; Table 1).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The connection the result of local knowledge together with soil, climate and the biotic environment which cannot be found elsewhere and obviously are required to be preserved from alien invasion (Barrionuevo et al , 2019; Garçon, 2019).…”
Section: Introductionmentioning
confidence: 99%